AKIBAT HUKUM PERNIKAHAN PADA MASA IDDAH DI DESA KEMANG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN BERDASARKAN KOMPILASI HUKUM ISLAM - Syafrida, Syafrida; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In Article 2 of the Compilation of Islamic Law, it is stated that marriage according to Islamic law is marriage, which is a very strong contract ot mitsaqan gholiidhan to obey Allah’s orders and carry out is worship. In Islamic law, there are several prohibited marriages, one of which is women who are still in the iddah period. However, not all Islamic teachings can be implemented properly. This is evidenced by the fact that there are partners who do not care about the iddah problem. Carrying out iddah for women is considered a form of worship. The purpose of writing this thesis, namely; First, the implementation of marriage during the Iddah period in the village of Kemang, Pangkalan Kuras district. Second, the legal consequences of marriage during the Iddah period.This type of research can be classified in the type of sociological research, because in this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study.From the research, there are three main points that can be concluded. First, the implementation of marriage during the iddah period is the same as marriage in general, it’s just that the marriage is carried out during the iddah period so that the marriage is invalid. Second, due to the law of marriage during the iddah period that will arise, the husband and wife will not get a marriage certificate, and when the marriage occurs, hereditary problems will arise. Author’s suggestion, First, it is hoped that the village government of Kemang needs socialization about marriage, especially marriage during the iddah period. Second, religious leaders should explore knowledge about the Marriage Law in Indonesia so that they can understand the procedures for marriage and divorce as regulated in the applicable Law.Keywords: Marriage-Iddah Perod-Compilation of Islamic Law